Pemberdayaan Usaha Mikro Kecil Menengah (UMKM) dalam Meningkatkan Kesejahteraan : Studi pada UMKM Binaan Rumah BUMN Aceh Utara - Minasiyah Minasiyah; Depita Kardiati; Muryali Muryali; Maryam Maryam; Risna Dewi (Sekolah Tinggi Ilmu Administrasi (STIA) Yappi Makassar, 2026)
The empowerment of Micro, Small, and Medium Enterprises (MSMEs) is a strategic effort to enhance the capacity and independence of business actors in supporting sustainable economic development. However, based on data from Rumah BUMN Aceh Utara, out of a total of 413 assisted MSMEs, only 9.16% have successfully upgraded their business status, while 90.84% have not yet done so. This study aims to describe MSME empowerment through the assistance program of Rumah BUMN Aceh Utara and to identify its supporting and inhibiting factors. This research employs a qualitative method with a descriptive approach. Data were collected through interviews, observations, and documentation involving Rumah BUMN managers and MSME actors, and were analyzed using the interactive model of Miles and Huberman. The results show that MSME empowerment in Rumah BUMN Aceh Utara is based on Suharto’s theory, which consists of three main approaches, namely empowering through training and mentoring that contributes to the improvement of business actors’ capacities, protecting through business legality facilitation, and supporting through the provision of production facilities, packaging machines, access to capital, promotion, and MSME gallery facilities, although these have not yet been fully optimized. The supporting factors of MSME empowerment include institutional support, technological development, and MSME participation, while the inhibiting factors include limited human resources, limited funding, and low participation of some MSME actors. This study emphasizes the importance of improving the quality of mentoring, optimizing the utilization of facilities, and increasing MSME participation to support the sustainability of empowerment programs.